PENERAPAN UJI TANAH DI LAPANGAN UNTUK SISWA SMKN 5 SURAKARTA PROGRAM KEAHLIAN TEKNIK KONSTRUKSI DAN PERUMAHAN - Rabinah, Aiun Hayatu; Goro, Garup Lambang; Harprastanti, Primasiwi; Mahbub, Jamal; Risman, Risman; Warsiti, Warsiti; Mulyono, Tedjo; Wiyana, Yustinus Eka; Nurhadi, Imam; Satriyadi, Lilik (Bangun Rekaprima, 2024)
SMKN 5 Surakarta students encountered a challenge during the initial assessment of the civil construction implementation, particularly concerning field soil testing. This challenge was exacerbated by the absence of soil mechanics courses in the curriculum. While the students possessed a fundamental grasp of civil engineering competencies, they faced difficulties in various aspects, with field soil testing being a notable area of concern. To address these competency gaps and enhance the vocational school curriculum, training sessions were conducted to educate students on the practical application of soil tests in the field. The specific training covered sand cone and DCP tests. According to the questionnaire results, post-training, over 50% of SMKN 5 Surakarta students exhibited a clear understanding of how to perform field tests using DCP, Sand Cone, and Speedy Moisture test equipment, along with the ability to analyze the resulting test data. The effectiveness of direct training and intensive mentoring was evident in facilitating students' comprehension of the provided material. Notably, 90% of the students affirmed that the training was easily comprehensible.